Die vrede van Münster/Westfale en die betekenis daarvan vir die vestiging van die gereformeerde godsdiens aan die Kaap - V. E. d'Assonville (Acta Theologica)
The significance of the Peace of Münster (as part of the more comprehensive Peace of Westphalia of 1648) is well-acknowledged within the European and Dutch historiography. In the South African writing of church history, however, this is not the case — not only is the epoch-making Peace of Münster nearly being neglected in general, but the relation between this central historical landmark on the one hand, and the founding of a refreshment post at the Cape of Good Hope by the DEIC in 1652 (with the consequential influence on the South African church history) on the other hand is almost ignored. The aim of this article is to demonstrate that 1652 as the founding date of the reformed religion at the Cape of Good Hope is historiographically not handled satisfactorily if the Peace of Münster is not sufficiently taken into consideration. The Peace Treaty finally enabled the Dutch to proceed — now for the first time in total freedom — with their sea voyages to India and the Far East. Thus an opportunity was created to found a refreshment post and eventually to further the reformed religion at the Cape.